Penatalaksanaan Holistik Pasien Laki-Laki Usia 57 Tahun Dengan Low Back Pain (LBP) Melalui Pendekatan Kedokteran - Yuliana; Dian Isti Angraini (Medula, 2023)
Low back pain is one of the common health problems that 50–80% of adults experience at some point in their life. The overall burden of LBP arising from ergonomic exposures at work was estimated at 21.8 million disability adjusted life years (DALYs). To apply the principles of family doctor medicine according to the problems found in patients in various aspects and carry out a holistic and comprehensive management that includes patient-centered, family approached, and community-oriented based on evidence-based medicine. This study is a case report. Primary data were obtained through autoanamnesis, physical examination and home visits, filling in family folders, completing family data, psychosocial and environmental data. Patient Mr. S, 57 years old, working as a mosque cleaner, came to Karang Anyar Primary Health Care, has a complaint of lower back pain since 2 months ago. The pain felt was like being stabbed and radiated to the patient's left leg. Initially, the patient admitted that the pain didn’t interfere with his work activities, but since the last 2 weeks before came to the Primary health care, the patient complained that the pain was getting worses and interfered with his activities. The patient was diagnosed as Low Back Pain (LBP). There are several factors that influence the patient's condition, namely internal and external risk factors. Holistic management with a family medicine approach is needed for patients with to low back pain to identify problems in various aspects in order to support the success of therapy.